Dual-layer sub-6GHz 5G communication FSS with triple band-stop characteristics - Sweta Panchal; M. Naresh Kumar; Shreenidhi H S; Prabhat Kumar Sahu; Muhammad Irsyad Abdullah; Jyoti Malik; D V S Ravi Varma; Udaybir Singh; A Bhowmik; A. Johnson Santhosh (Results in Engineering)
This article presents a simple and compact dual metallic layer triple band-stop 2D frequency selective surface (FSS). The design consists of four 90° rotational symmetric rectangular and triangular spiral inductive arms implemented on the top and bottom metallic layer of flame retardant-4 (FR4) dielectric substrate, respectively. To increase the electrical path length of the proposed design, these spiral inductive arms are interconnected at the center. Moreover, an inductive grid is imprinted at the top metallic layer to boost the filtering behaviour of the proposed structure. The proposed design exhibits triple band-stop response at sub-6 GHz 5th generation (5 G) bands new radio (NR) n39/40, long term evolution (LTE) 42/LTE43 and LTE 46. With the dimensions of 6 × 6 mm2, the proposed design provides a minimal footprint of 0.039λ × 0.039λ, here λ corresponds to the first transmission zero frequency. This design achieves at least 33 % size reduction compared to similar designs in the literature. The simulated FSS behaviour is verified by measuring the results of fabricated FSS prototype, which consists of 900 elements arranged in a 30 × 30 square lattice. This rotational symmetric and miniaturized design manifests polarization-independent characteristics with high angular stability at both normal and oblique incidence angles. The proposed triple band-stop FSS can be used for the electromagnetic shielding of sub-6 GHz 5 G communication systems.